Breeding Performance and Nursery Practices of Labeo Bata (Hamilton-Buchanan, 1822) - Hossain, Quazi Zahangir; Hossain, M Altaf; Parween, Selina (Scientific World, 2010)
A study was conducted to observe the breeding performance and nursery practices of the threatened indigenous fish species Labeo bata in Jessore (Longitude: 89°122 003 East; Latitude: 23°102 453 North), Bangladesh during 1998 to 2002. Eight trial doses of PG (Pituitary Gland) used for induced breeding of L. bata were 1.0mgPG/kg in the first dose, and 1.0 to 8.0mgPG/kg in second dose for female. On the other hand, five trial doses were administered for the male to identify the suitable single dose (1.5mgPG/kg) only. The best performance was obtained with 5.0mg of PG/kg body weight in the second dose for female of wild and successive three generations. The highest growth (lt.: 19.37mm and wt.: 57.67mg) and survivability (63.33%) of the fish fry was observed by using rice bran and mustard oil cake after 10 days of nursing. Key words: Breeding performance; Nursery practices; Threatened species; Labeo bata. DOI: 10.3126/sw.v5i5.2654 Scientific World, Vol. 5, No. 5, July 2007 40-45